Treating a College-Aged Patient with Neuropsychological Problems and ADHD: Discussion of Dr. Whitman's Analysis of Mark. Issue 1 (1st January 2019) - Olesker, Wendy
ABSTRACT: The central thesis of this discussion is that an adolescent psychoanalyst—someone who understands development, developmental interference, unconscious conflict, and neuropsychiatric impairment—is especially well-suited to treat patients with attention deficit hyperactivity disorder, learning disabilities, and behavior problems. Candidates in such training programs are provided with the didactic instruction and supervision necessary to grasp the kind of multimodal treatment approach that is necessary for these patients. A focus on enhancing inner processing and reflectiveness, building the tools for strengthening executive functioning, and clearing away maladaptive defenses all help to stimulate feelings of becoming an active agent on one's own behalf. Furthermore, facilitating integration and activating the questioning and evaluating parts of one's mind to reshape inner standards and values is a principal component of the therapeutic work. This also includes separating from primitive parental introjects, which creates more stable autonomy and the ability to face one's limitations in small doses, thus leading to amelioration through new experience and the transforming of emotions into modulated, helpful signals.